Green Product, Green Brand Image, Green Advertising on Purchase Decisions Mediated by Price, SERVQUAL - Dewi Puspaningtyas Faeni; Herni Pujiati; Dewi Sri Wulandari (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study aims to analyze the effect of green product, green brand image, and green advertising on purchase decisions at Photovoltaic Industry, with price and SERVQUAL as mediating variables. The objective is to understand how green marketing strategies determined purchase decision upon renewable energy sector.Research Methodology: The research was conducted at Photovoltaic Industry, using a quantitative approach. Collected 109 respondents Slovin’s formula. The statistic analysis employed Structural Equation Modeling (SEM) with SmartPLS 4.2 software.Results: Green product, green brand image, and green advertising have a positive and significant effect on purchase decisions, both partially and simultaneously. Price and SERVQUAL proven as mediators determined green marketing strategies on consumer purchasing behavior.Conclusions: The study concludes that integrating green marketing strategies with competitive pricing and high service quality can significantly enhance purchase decisions at Photovoltaic Industry. This highlights the importance of combining environmental values with practical business elements.|Limitations: The study is limited to one Photovoltaic company and a relatively small sample size of 109 respondents, which may restrict the generalization of findings to other industries or regions.|Contributions: This research contributes to the field of marketing management and sustainability studies by providing empirical evidence on the role of green marketing in consumer decision-making. It offers practical implications for business practitioners, policymakers, and academics in developing strategies that align environmental responsibility with improved organizational performance based on renewable energy.